Are differences in discourse patterns relevant for the participants of interactions in English as a lingua franca? - Nowicka, Agnieszka (Investigationes Linguisticae, 2019)
Intercultural differences in discourse patterns have been considered the most important cause of communication problems. It is less certain if these differences are relevant for talk participants in handling communication problems in intercultural interactions. The aim of the case study presented in this paper is observing if talk participants orient to intercultural differences in discourse patterns and what knowledge of these differences they have. I use ethnomethodological approach in analyzing the interaction of Polish students with their Chinese interlocutor. The interactions is an interview conducted in English as a lingua franca. I also conduct an ethnographic interview with the Polish speakers to study their knowledge concerning communication problems which appeared in their interactions with the Chinese speaker. Analyzing the ethnographic interview as interaction, I focus on the content co-construed by the interview participants.